Energy use and emissions reduction strategies for structural steel fabricators: a case study - Bergstrom, Erik Anderson, author; Guggemos, Angela Acree, advisor; Criswell, Marvin E., committee member; Hamzeh, Farook, committee member (Colorado State University. Libraries, 2010)
Energy price escalation, natural resource depletion, and wide-spread environmental degradation are driving demand for more sustainable construction methods and materials. Steel fabricators working to operate more sustainably require detailed energy and environmental analysis of operational practices in order to make informed improvements. Yet only limited research exists on the energy use and emissions associated with fabrication and material sourcing for structural steel used in building construction. This research involves a life-cycle inventory assessment of structural members used in a case-study building to address this gap in research and identify high-impact areas for future process improvement at one fabrication facility. With a life-cycle inventory model developed, feasible process improvements are measured against standard practices, and the associated energy savings and environmental improvements are identified. The main discovery of this research is that while the fabricator has the ability to make significant energy and emissions reductions by modifying operational process within their own facility, the most impactful opportunities are in material selection alternatives, such as sourcing reused materials. Structural steel fabricators can use these findings to reduce environmental impacts and operating costs, while delivering a more environmentally preferable product.
Keywords: sustainability; steel; life cycle assessment; LEED; fabrication; energy; Structural steel industry -- Environmental aspects; Leadership in Energy and Environmental Design Green Building Rating System; Scrap metals -- Recycling; Industrial ecology; Sustainable construction